2017
DOI: 10.1149/2.1091704jes
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Electrochemical Formation of Magnetite Nanoparticles

Abstract: The electrochemical mechanism of the formation of magnetite nanoparticles is studied. The proposed mechanism suggests the formation of iron hydroxide Fe(OH) 2 in the presence of oxygen which produces lepidocrocite (γ-FeOOH) followed by its chemical dehydration. This is in contrast to other reported mechanisms that suggest the reduction of Fe(OH) 3 at the cathode. Video frames captured during the electrosynthesis of magnetite, in a typical two-electrode cell, indicate that the nanoparticles form in the region c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 37 publications
4
56
0
Order By: Relevance
“…The last mechanism which involves dissolved oxygen as an oxidizing agent for Fe(OH) 2 in solution to produce magnetite seems to be the most likely appropriate to describe the electrochemical formation of magnetite nanoparticles. This mechanism was first proposed by Fajaroh F. et al (2012), and the validity was confirmed by Lozano I. et al (2017) …”
Section: Mechanism Of Particle Formationmentioning
confidence: 67%
See 3 more Smart Citations
“…The last mechanism which involves dissolved oxygen as an oxidizing agent for Fe(OH) 2 in solution to produce magnetite seems to be the most likely appropriate to describe the electrochemical formation of magnetite nanoparticles. This mechanism was first proposed by Fajaroh F. et al (2012), and the validity was confirmed by Lozano I. et al (2017) …”
Section: Mechanism Of Particle Formationmentioning
confidence: 67%
“…As noted by Lozano I. et al (2017), however, it is unlikely that solid species such as Fe(OH) 3 can reach the cathode to undergo reduction. Additionally, due to its high propensity to escape from the reacting medium, it is almost impossible for hydrogen gas to react with iron hydroxide (Eqn.…”
Section: Mechanism Of Particle Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…[18][19][20][21][22][23][24][25] In most instances, known electrochemical approaches for the synthesis of nanoparticles [26][27][28] involve the growth of lms onto inert substrates, mostly by one-step electrodeposition, at working temperatures between 70 and 90 C. A compilation of pathways and methods for the electrochemical formation of magnetite nanoparticles is available in the scien-tic literature. 23,26,[29][30][31][32] In the present study, a new electrochemical method, called gas-diffusion electrocrystallization (GDEx), 14 is employed for the formation of iron oxide nanoparticles (IONPs) 33 from a soluble iron precursor (Fe 2+ ). A gas diffusion cathode is used for the electroreduction of oxygen (O 2 ) contained in a gas phase (air) which, in turn, drives the precipitation of crystalline IONPs at the electrochemical interface.…”
Section: Introductionmentioning
confidence: 99%